Екологічний стан міста Луцька - Потапова, Алла Геннадіївна; Ільїна, Мар'яна; Potapova, Alla H.; Ilina, Mariana (Східноєвропейський національний університет імені Лесі Українки, 2014)
Проаналізовано екологічний стан міста Луцька. Виділено фактори, які негативно впливають на результати дослідження і на екологічну ситуацію міста Луцьк. Виявлено джерела надходження в атмосферне повітря забруднюючих речовин, зміну хімічного складу повітря.

The ecological state of city of Lutsk is analysed. In particular, factors, that negatively influence both on the results of researches and on the ecological situation of city, are distinguished. Entering sources are enumerated atmospheric air of contaminents, change of chemical composition of air in 2013 as compared to the last years. The basic districts of contamination of atmospheric air, ground cover, surface-water are considered, most loaded territories from radiation and thermal pollutants. Characterized their adverse health effects Lutsk. Near-term measures are offered and those that was already conducted for overcoming of ecological tension in city to Lutsk are distinguished. On the basis of basic statistical indexes, a shortterm analysis is done in relation to the change of ecological position
Ecological State of the City of Lutsk
Keywords: екологія; екологічна безпека; екологічне становище; індекс забруднення; навколишнє середовище; ecology; environmental safety; environmental condition; an index of pollution; environmen